MEMBANGUN KONSISTENSI BELAJAR MELALUI SELF CONTROL DAN SELF CONSCIOUSNESS - Muhammad Fadhil Alghi Fari Majid (PAI RAFAH, 2021)
Consistent with oneself is not easy as it said that the ups and downs of consistency in individuals often become problematics in life, especially in learning. Developing consistency in learning is quite difficult to be realized in humans. The problem is also felt by the writer. Weak consistency in learning will have a negative impact on humans, especially for the younger generation. There are several things that can be done in building consistency of learning, namely through self control and self consciousness.This research is a type of library research method used is data management and data sources using documentation studies, observations of books, paper articles, journals, magazines, internet, or matters that are relevant to the main topic of research, and analyze data. The purpose of this paper is to provide more motivation for the main reader for the writer in building consistency in learning with humans. By using library research, the writer can conclude that it turns out that self control and self consciousness can build consistency in learning. Because with self control and self consciousness is able to bring up control of yourself and be able to bring up self-awareness so that it is easier to motivate someone in building a consistent human learning.